1990
DOI: 10.1136/gut.31.9.1046
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cholinergic neuroeffector transmission of ganglionic and aganglionic colon in Hirschsprung's disease.

Abstract: Differences in the release and content of acetylcholine and the a2 adrenoceptor mediated interaction between noradrenergic and cholinergic neurons were investigated by neurochemical and pharmacological methods in aganglionic and ganglionic segments of isolated human colon taken from children suffering from Hirschsprung's disease. Both at rest and during transmural stimulation the release of acetylcholine was significantly higher in the spastic (aganglionic) segment than in the proximal dilated bowel. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The abnormalities of ICCs may cause the reduction in the nitric oxide synthesis, which in turn leads to the spasm of the bowel muscle. Spasm of the gut has also been observed in HSCR patients [41]. Therefore, it is postulated that there is a relationship between the poor development of ICC and bowel spasm that leads to megacolon.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormalities of ICCs may cause the reduction in the nitric oxide synthesis, which in turn leads to the spasm of the bowel muscle. Spasm of the gut has also been observed in HSCR patients [41]. Therefore, it is postulated that there is a relationship between the poor development of ICC and bowel spasm that leads to megacolon.…”
Section: Discussionmentioning
confidence: 99%
“…In the aganglionic segment, therefore, accumulation of the enzyme acetylcholinesterase is excessive, resulting from continuous acetylcholine release from the axons of the extramural parasympathetic ganglion. Pharmacologic investigations of the colon in HD patients bave demonstrated higher acetylcholine release in the aganglionic segment at rest and after stimulation than in the proximal ganglionic bowel [49,50]. It is suggested that in HD the increased acetylcholine release, the enhanced sensitivity of smooth muscle cells to acetylcholine, and the lack of a2-adrenoreceptormediated noradrenergic modulation of acetylcholine release from cholinergic interneurons might be responsible for the spasm of aganglionic segment.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The way forward to diagnosis both Hirschsprung's disease and these associated problems may be by immunocytochemical means [19], since there ap pears to be both smooth muscle and neuronal abnormalities present in some even if gan glion cells are seen [23,26,105], It would appear that minute changes in the micro-envi ronment may produce Hirschsprung's and similar diseases [106,107], 112 …”
Section: The Futurementioning
confidence: 99%
“…A reduction in neuro peptides in the aganglionic segment [24] has also been demonstrated. Cholinergic innerva tion is absent in aganglionic bowel [25] and with the increased acetylcholine release may account for the spasm [26], Abnormalities can be demonstrated with specific markers [27] and antibodies to neurofilament polypeptides [28], These abnormalities would suggest that an abnormal environment has a role in the pathogenesis of Hirschsprung's disease [29],…”
mentioning
confidence: 99%